(untitled) - Phillips, Derek (New York, 1997)
Modern lighting techniques help you showcase and beautify historic buildings! Now you can design better, more efficient illumination for older structures with Lighting Historic Buildings by Derek Philips. You'll know how to incorporate modern lighting into buildings built decades--or centuries--before flourescent bulbs, TV screens, computer monitors and OSHA requirements were invented. Whether you're renovating, refurbishing or expanding an illumination system, lighting historic buildings shows you proven strategies and designs for using both natural and artificial light to achieve outstanding results. Plus, over 200 full color illustrations show you the best lighting solutions for offices, residences, churches, industrial facilities, and change-of-use properties worldwide. Uding the expert techniques you'll find in this one-of-kind resource, you'll see how to provide modern and efficient lighting designs while retaining the original beauty and integrity of historic buildings.
Keywords: Lighting,Historic buildings,Ánh sáng,Lịch sử tòa nhà; History,Lighting,Lịch sử,Ánh sáng; United States,Hoa Kỳ